Application of Hydroxyapatite scaffold from Portunus pelagicus on OPG and RANKL expression after tooth extraction of Cavia cobaya - Michael Josef Kridanto Kamadjaja, - (RJPT, 2021)
Objective: This study was to determine OPG and RANKL expression after hydroxyapatite (HA) scaffold from crab shells (Portunus pelagicus) application in tooth socket of Cavia cobaya. Methods: This study was a post-test only control group design. Twenty four Cavia cobaya was divided into 4 groups. The lower left incisor was extracted and given a combination of HA and gelatin scaffold. Experimental animals were sacrificed on the 7th and 14th day. The amount of OPG and RANKL expression was calculated under a light microscope at 1000x magnification. The statistical analysis was done by One Way ANOVA Test and Tukey HSD. Results: Compared to other groups, the lowest and the highest level of OPG and RANKL were in P14 group. Conclusion: HA scaffold from crab shells (Portunus pelagicus) can increase OPG expression and decrease RANKL expression in the process of regenerating alveolar bone after tooth extraction.